Knowledge is the key - Abd Razak, Dzulkifli (2005)
knowledge and education so that the individual or the nation is prepared for future global challenges. It encourages the doors of ijtihad (thorough study) to be opened, so that interpretations are in tandem with the developmental needs of the prevailing tune and conditions. In order to put Islam Hadhari into practice with a civilisational framework, the heritage of Islamic civilisation that unfolded on the stage of history can be a useful reference point and become the source of inspiration for society to learn from and emulate. A change in attitude and culture requires ijtihad and Jihad (struggle) on a broader interpretation, covering all aspects of life, including the pursuit of knowledge, mastery of science and technology and economic activity.